Regional stratigraphy of the south polar layered deposits (Promethei Lingula, Mars): "Discontinuity-bounded" units in images and radargrams - Guallini, Luca; Rossi, Angelo Pio; Forget, François; Marinangeli, Lucia; Lauro, Sebastian Emanuel; Pettinelli, Elena; Seu, Roberto; Thomas, Nicolas (Icarus, 2018)
The Mars South Polar Layered Deposits (SPLD) are the result of depositional and erosional events, which are marked by different stratigraphic sequences and erosional surfaces. To unambiguously define the stratigraphic units at regional scale, we mapped the SPLD on the basis of observed discontinuities (i.e., unconformities, correlative discontinuities and conformities), as commonly done in terrestrial modern stratigraphy. This methodology is defined as "Discontinuity-Bounded Units" or allostratigraphy, and is complemented by geomorphological mapping.Our study focuses on Promethei Lingula (PL) and uses both high-resolution images (CTX, HiRISE) and radargrams (SHARAD) to combine surface and sub-surface observations and obtain a 3D geological reconstruction of the SPLD. One regional discontinuity (named AUR1) was defined within the studied stratigraphic succession and is exposed in several non-contiguous outcrops around PL as well as observed at depth within the ice sheet. This is the primary contact between two major depositional sequences, showing a different texture at CTX resolution. The lower sequence is characterized mainly by a "ridge and trough" morphology (Ridge and Trough Sequence; RTS) and the upper sequence shows mainly by a "stair-stepped" morphology (Stair-Stepped Sequence; SSS). On the basis of the observations, we defined two regional "discontinuity-bounded" units in PL, respectively coinciding with RTS and SSS sequences. Our stratigraphic reconstruction provides new hints on the major scale events that shaped this region. Oscillations in Martian axial obliquity could have controlled local climate conditions in the past, affecting the PL geological record.